2005
DOI: 10.1007/s10164-004-0138-y
|View full text |Cite
|
Sign up to set email alerts
|

Egg cannibalism in Ascia monuste in the field; opportunistic, preferential and very frequent

Abstract: Newly hatched caterpillars of the specialist herbivorous species Ascia monuste (Lepidoptera, Pieridae) feed on egg chorion before ingesting plant material. They also ingest their exoskeletons and perform egg cannibalism in both the field and the laboratory. Females lay eggs on plants which already have conspecifics (eggs and/or caterpillars) leading to the observation of cannibalism in the field. Two favorable conditions are required for such an occurrence: (1) eggs laid close together on the same leaf, and (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
1
13
0
1
Order By: Relevance
“…In other words, the objective was to avoid any other food resource than the eggs, in order to give the caterpillars a greater propensity toward cannibalism and consequently preference for kin or nonkin. The occurrence of egg cannibalism in caterpillars of Lepidoptera even in the presence of an adequate plant resource has been found in Helicoverpa zea (Noctuidae) (Joyner and Gould 1985), H. armigera (Sigsgaard et al 2002), and Ascia monuste (Pieridae) (Barros-Bellanda and Zucoloto 2005).…”
Section: Resultsmentioning
confidence: 98%
“…In other words, the objective was to avoid any other food resource than the eggs, in order to give the caterpillars a greater propensity toward cannibalism and consequently preference for kin or nonkin. The occurrence of egg cannibalism in caterpillars of Lepidoptera even in the presence of an adequate plant resource has been found in Helicoverpa zea (Noctuidae) (Joyner and Gould 1985), H. armigera (Sigsgaard et al 2002), and Ascia monuste (Pieridae) (Barros-Bellanda and Zucoloto 2005).…”
Section: Resultsmentioning
confidence: 98%
“…At an individual level, cannibalism has been suggested to have several benefits, the most important being nutritional [2, 16]. The additional food gained has been shown to increase development rate, survival and fertility of cannibals in several arthropod species [1, 3, 7].…”
Section: Introductionmentioning
confidence: 99%
“…The additional food gained has been shown to increase development rate, survival and fertility of cannibals in several arthropod species [1, 3, 7]. In the pierid Ascia monuste cannibal caterpillars showed higher survival rate and weight than noncannibal ones [16]. Likewise, in Drosophila melanogaster larvae, it was shown that an exclusively cannibalistic diet was sufficient for normal development from eggs to fertile adults [17].…”
Section: Introductionmentioning
confidence: 99%
“…A single laying of these females may be as large as 60 eggs, which are usually distributed in many plants in nature (Catta-Preta & Zucoloto 2003). However, females may oviposit on plants which already have conspecifics (eggs and/or caterpillars) (Barros-Bellanda & Zucoloto 2005) leading to the occurrence of egg cannibalism. Egg cannibalism is observed in both field and laboratory and it may also occur in the presence of abundant food (BarrosBellanda & Zucoloto 2005).…”
mentioning
confidence: 99%